2008
DOI: 10.1016/j.ccr.2008.01.034
|View full text |Cite
|
Sign up to set email alerts
|

HIF1α Induces the Recruitment of Bone Marrow-Derived Vascular Modulatory Cells to Regulate Tumor Angiogenesis and Invasion

Abstract: Development of hypoxic regions is an indicator of poor prognosis in many tumors. Here, we demonstrate that HIF1alpha, the direct effector of hypoxia, partly through increases in SDF1alpha, induces recruitment of bone marrow-derived CD45+ myeloid cells containing Tie2+, VEGFR1+, CD11b+, and F4/80+ subpopulations, as well as endothelial and pericyte progenitor cells to promote neovascularization in glioblastoma. MMP-9 activity of bone marrow-derived CD45+ cells is essential and sufficient to initiate angiogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
909
0
14

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,037 publications
(956 citation statements)
references
References 56 publications
33
909
0
14
Order By: Relevance
“…The GL261-Quad cell line is engineered to express the model antigens human gp100 [25][26][27][28][29][30][31][32][33] , chicken OVA 257-264 , chicken OVA [323][324][325][326][327][328][329][330][331][332][333][334][335][336][337][338][339] , and mouse alloantigen I-Ea [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] . Female 6-8-week-old C57BL/6 mice (The Jackson Laboratory, Bar Harbor, ME, USA) were inoculated by stereotactic injection of 6.0×10 4 -1.0×10 5 GL261 or GL261-Quad cells into the right striatum.…”
Section: Gl261 Tumor Implantationmentioning
confidence: 99%
“…The GL261-Quad cell line is engineered to express the model antigens human gp100 [25][26][27][28][29][30][31][32][33] , chicken OVA 257-264 , chicken OVA [323][324][325][326][327][328][329][330][331][332][333][334][335][336][337][338][339] , and mouse alloantigen I-Ea [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] . Female 6-8-week-old C57BL/6 mice (The Jackson Laboratory, Bar Harbor, ME, USA) were inoculated by stereotactic injection of 6.0×10 4 -1.0×10 5 GL261 or GL261-Quad cells into the right striatum.…”
Section: Gl261 Tumor Implantationmentioning
confidence: 99%
“…More recent studies have shown that TAMs are recruited to experimental tumors following different forms of anti-angiogenic therapies [138][139][140], often because of the hypoxia-induced increase in chemotactic factors [94,138]. Various studies have reported that TAMs counteract the efficacy of anti-angiogenic agents.…”
Section: Immune Cell Function Following Vascular-targeting Agentsmentioning
confidence: 99%
“…In mice, radiotherapy-induced TAM infiltration is mainly attributed to radiation-induced hypoxia and the subsequent surge in hypoxia-regulated chemokines, such as CXCL12 [90,93]. Monocytes and macrophages expressing TIE2 -the receptor for Angiopoietins 1 and 2 -are highly receptive to increased hypoxia and CXCL12 levels [90,93,94], and TIE2-expressing monocytes/macrophages 10 have a profound ability to counteract hypoxia through the induction of angiogenesis [95]. As one may predict, neutralizing CXCL12 or blocking its receptor, CXCR4, to prevent TAM accumulation further delays tumor progression when combined with radiotherapy in orthotopic syngeneic and xenograft models of glioblastoma [90], as well as subcutaneous xenografts of lung carcinoma and syngeneic mammary tumors [93].…”
mentioning
confidence: 99%
“…[4][5][6][7] Considered chief among these is VEGF, which may be upregulated via multiple angiogenesispromoting pathways. In hypoxic conditions, commonly found as tumors outgrow their intrinsic blood supply, hypoxiainducible factor 1a accumulates and ultimately increases VEGF stabilization.…”
Section: Angiogenesis and The Role Of Antiangiogenesis In Patients Wimentioning
confidence: 99%